Comparison of Properties of Stem Cells Isolated from Adipose Tissue and Lipomas in Dogs - Takahiro Teshima; Akito Matsuoka; Maika Shiba; Kazuho Dairaku; Hirotaka Matsumoto; Ryohei Suzuki; Hidekazu Koyama (Stem Cells International)
Adipose-derived mesenchymal stem cells (ADSCs) have been suggested their benefits in regenerative medicine for various diseases. Lipomas, benign neoplasms in adipose tissue, have been reported as a potential source of stem cells. These lipoma-derived mesenchymal stem cells (LDSCs) may be useful for regenerative medicine. However, the detailed characteristics of LDSCs have not been fully elucidated. This study investigated the cellular proteomics and secretomes of canine LDSCs in addition to morphology and proliferation and differentiation capacities. Some LDSCs isolated from canine subcutaneous lipomas were morphologically different from ADSCs and showed a rounded shape instead of fibroblast-like morphology. The phenotype of cell surface markers in LDSCs was similar to those in ADSCs, but CD29 and CD90 stem cell markers were more highly expressed compared with those of ADSCs. LDSCs had noticeably high proliferation ability, but no significant differences were observed compared with ADSCs. In regard to differentiation capacity compared to ADSCs, LDSCs showed higher adipogenesis, but no differences were observed with osteogenesis. Cellular proteomic analysis using two-dimensional gel electrophoresis revealed that over 95% of protein spots showed similar expression levels between LDSCs and ADSCs. Secretome analysis was performed using iTRAQ and quantitative cytokine arrays. Over 1900 proteins were detected in conditioned medium (CM) of LDSCs and ADSCs, and 94.0% of detected proteins showed similar expression levels between CM of both cell types. Results from cytokine arrays including 20 cytokines showed no significant differences between CM of LDSCs and that of ADSCs. Our results indicate that canine LDSCs had variability in characteristics among individuals in contrast with those of ADSCs. Cellular proteomics and secretomes were similar in both LDSCs and ADSCs. These findings suggest that LDSCs may be suitable for application in regenerative medicine.